Ownership Structure And Risk Management Moderated By Audit Committee On Firm Performance - Fauzan, Muhammad; Amanda Jonatan Puteri; Hendro Prasetio; Henny Setyo Lestari; Farah Margaretha (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of managerial ownership, ownership concentration, institutional ownership, and enterprise risk management on firm performance before and after moderated by audit committee. This study used consumer and non consumer cyclicals sector companies listed on the Indonesia Stock Exchange in 2018-2022. Samples were selected by purposive sampling method and the data used were 235 data. The data obtained was processed using the E-Views 13 program to analyze panel data regression. Based on research conducted, the results are managerial ownership, ownership concentration, and institutional ownership has a positive significant effect on firm performance. After moderated by audit committee, managerial ownership and ownership concentration negatively moderated on firm performance. As a control variable, firm size and leverage has a negative significant effect on firm performance.